ANALISIS PENGARUH KOMPENSASI, BEBAN KERJA, DAN STRES KERJA TERHADAP KOMITMEN ORGANISASIONAL (STUDI PADA TENAGA PEMASAR MIKRO PT BANK RAKYAT INDONESIA (PERSERO) TBK, CABANG PRAYA) - Fatmawati Fatmawati (Master of Management, Mataram University, 2017)
The purpose of this research is to examine the significant partial effect of compensation on organizationalcommitment, work load on organizational commitment, work stress on organizational commitment, and toexamine the significant simultant effect of compensation, work load, work stress, on organizational commitmenton micro credits marketings of PT Bank Rakyat Indonesia Tbk (Persero) Praya. This is an associative research.Technik sampling is census method, the amount of sample in this research of 60 respondents. Data were analyzedby Multiple Regressions. The result shows that compensation has significant effect on organizationalcommitment, work load has significant effect on organizational commitment, work stress has significant effectorganizational commitment, and compensation, work load, work stress has significant simultant effect onorganizational commitment, and work stress has dominant effect on organizational commitment on micro creditsmarketings of PT Bank Rakyat Indonesia Tbk (Persero) Praya.Keywords: Compensation, Work Load, Work Stress, and Organization Commitment